Role of ABCC2 Gene Polymorphism on Deferasirox Hepatic Toxicity in Thalassemia Patients - Hussain , Zahraa; Mosa , Amal Umran; Atiyeh , Mohammed Nnaji; Sahib, Ahmed Salih (Journal of Contemporary Medical Sciences, 2024)
Objectives: To investigate the relationship between ABCC2 gene polymorphism (G>A, rs 8187710) and (C>T, rs 717620) and hepatotoxicity in thalassemia patient treated deferasirox . Methods: The present work included a cross sectional study, 100 patients suffering iron overload and thalassemia out of 650 patients in (thalassemia center) and 100 healthy patients to compare the parameters of liver function tests of thalassemia patients with healthy group. The allele specific polymerase chain reaction technique (pcr) was used to detect the (G>A, rs 8187710) and (C>T, rs 717620 single nucleotide polymorphism (SNP). Results : 58 patients with rs 8187710 who are wild (GG) and 32 patients hetero(GA)and 56 patients with rs 717620 who wild (CC) and 31 hetero (CT) are exposed to hepatotoxicity than patients with homo groups Conclusion: According to the results of the currents study, the (G>A, rs 8187710) and (C>T, rs 717620) single nucleotide polymorphism (SNP) was associated with hepatotoxicity in patients treated deferasirox.